Paket Program, Indeks Prestasi Kumulatif, Umur dan Domisili sebagai Faktor Pembeda Prestasi Akademik Mahasiswa - Supriyanto Supriyanto; Dewi Anggraini; Fahmi Sulaiman; Elserra Siemin Ciamas; Yeni Rachmawati (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
One measure of success in teaching and learning in tertiary institutions is academic achievement. Through student academic achievement, it will increase the enthusiasm of prospective students in determining the tertiary institution of their choice. This research is aimed to determine the differentiating factors of student academic achievement, with the independent variables, namely Program Package, Grade Point Average (GPA), Age and Domicile. The research conducted included classifying students into two groups based on student academic achievement, so the analysis method used was Discriminant Analysis. The results revealed that the differentiating variables between groups consisted of (1) Grade Point Average and (2) Age. The results of data processing from the Enter / Removed Variables, it is known that the Grade Point Average (GPA) variable can be included in the discriminant equation formation process, while the Program Package, Age, and Domicile variables cannot be included in the discriminant equation formation. Eigenvalues test results, obtained a Canonical Correlation value of 0.852 so that the Square Canonical Correlation (CR2) = (0.852) 2 = 0.7259, it can be concluded that the Student Academic Achievement Variable can be explained by the Variable Program Package, Student Achievement Index (GPA), Age and domicile of 72.59%. The results of the validation state that the level of accuracy is> 50% so that the discriminant function is considered appropriate in classifying students.